EMPOWERMENT OF CHILDREN IN MADRASAH DINIYAH THROUGH ECOLOGICAL THEOLOGY-BASED GREEN MOVEMENT - Muflikhatul Khoiriyah, Indri; Kamelia, Risantika; Umaknun, Lulu; Susanti, Susi; Susanti, Suparti (Universitas Darunnajah, Jakarta, Indonesia, 2025)
Environmental degradation is a critical issue requiring involvement from various sectors, including religious education. Madrasah Diniyah holds strategic potential to foster children’s ecological awareness by integrating spiritual values within ecotheology principles. This empowerment program for Madrasah Diniyah children through an ecotheology-based greening movement employed Participatory Action Research (PAR), actively involving children, teachers, and the community. Findings revealed an increased understanding among children of the relationship between religion and environmental conservation, alongside the growth of spiritual awareness influencing environmentally friendly behaviors. The program serves as an effective educational model for developing ecological and religious character from an early age. Planned follow-ups and evaluations aim to ensure sustainability and broaden the program’s impact as a contribution to environmental preservation and sustainable community empowerment. Synergistic collaboration among educational institutions, communities, and partners is key to this program’s success